Percutaneous Coronary Intervention Versus Optimal Medical Therapy for Severe Ischemic Left Ventricular Systolic Dysfunction - Ruth A. Mathew Kalathil, MD; Akshay Machanahalli Balakrishna, MD; Ahmed El-Shaer, MD; Andrew M. Goldsweig, MD, MS; Khagendra Dahal, MD; Saraschandra Vallabhajosyula, MD, MSc; Ahmed Aboeata, MD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2024)
Coronary artery disease is the most common cause of heart failure, which is the leading cause of cardiovascular-related death worldwide. There are insufficient data to make strong recommendations for percutaneous coronary intervention (PCI) in patients with severe ischemic left ventricular systolic dysfunction (LVSD). In that context, we performed a meta-analysis to compare the outcomes of PCI with those of optimal medical therapy alone in patients with severe ischemic LVSD. A systematic search was conducted in PubMed, EMBASE, and ClinicalTrials.gov from inception to December 2023. Our outcome of interest was all-cause mortality in patients undergoing PCI vs medical therapy. We used random effects models to aggregate data and to calculate pooled incidence and relative risk with 95% CIs. Four studies including 2 randomized controlled trials with 2080 patients (PCI, 1082; optimal medical therapy, 998) were included. All-cause mortality did not differ significantly between the groups: 168 patients (15.5%) in the PCI group vs 200 patients (20.0%) in the optimal medical therapy group (relative risk, 0.88; 95% CI, 0.75-1.09; P=.25). In conclusion, the available evidence indicates that PCI does not improve all-cause mortality in patients with severe LVSD without lifestyle-limiting anginal symptoms. Further data are needed to identify subgroups of patients better served by each modality.